PKM Pelatihan Dan Implementasi Software Perpajakan Terintegrasi Bagi Wajib Pajak Pribadi Dan Badan Usaha - Kaslani; Rudi Kurniawan; Saeful Anwari; Rano; Ghali Rizki Lesmana (CV. Multi Kreasi Media, 2022)
In the current era of digitalization, taxation is a crucial aspect of financial management that requires special attention from taxpayers, both individuals and businesses. However, many still face difficulties in effectively and efficiently managing their taxes. This issue is exacerbated by a lack of understanding of modern integrated tax technology. Therefore, this research aims to provide training and implementation of integrated tax software designed to simplify the tax filing and reporting process. The methods used in this program include face-to-face training and technical assistance in using tax software that complies with Indonesian tax regulations. The results of this program are expected to enhance taxpayers' ability to manage their tax obligations, reduce the risk of errors in reporting, and increase time and cost efficiency. This program is also expected to support the successful implementation of independent tax obligations by taxpayers.